Tuesday

July 22, 2014

July 22, 2014

Posted by **Helen** on Thursday, October 10, 2013 at 8:21pm.

y=x(ab/a-b)

- Math -
**Swaastikaa**, Friday, October 11, 2013 at 3:09amHi Helen, this is easy!

Solving the literal equation for 'a' means expressing the equation in terms of a.

Let us see the solutions step by step:

a) Multiplying the denominator a-b with y gives : y(a-b) = xab

b)Expanding the parentheses y(a-b) gives ya-yb = xab

c)Since ya and xab have 'a', the equation is now rearranged as:

ya-xab = yb

d)Taking out the 'a' from ya-xab

ya-xab = a(y-xb)

e) a(y-xb) = yb

a = yb/(y-xb)---> final answer

**Related Questions**

math, algebra - How do I solve for the following: Directions solve each literal ...

Maths - solve the following pair of simultaneous equation: (x/a)+(y/b)=1 (x/b)+(...

Math - Solve each literal equation for the indicated variable. 4x-5y=10 for y (...

math,algebra - How do you solve these types of math problems. Directions: Solve ...

math, beginning algebra - can someone correct this for me. Directions: Solve ...

math - someone please help please help don't understand solve each literal ...

bobpursly,.math - Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each ...

Math - I just don't understand this question: h(t)=A*b^x h(3)=4 h(5)=40 Solve ...

Literal Equation - how to solve 6=hj+k for j

Math - Solve each literal equation for the indicated variable 2x-3y=4 for x The ...